(untitled) (Al-Academy, 2017)
With the massive presence of the critical approaches &, artistical School, movements, methods, Concepts, & theories, which came to take its chance from arts in general view & the plastic arts in special view. The Searches of fine arts & what this methods present from excitement become the point for many questions, & go to the purposes to be useful. For the artistic Work to come out in aesthetic image, especially on the subject of reading& reception, & entering it into layout of multiple relationships, for the artistic Work to be more simulation of the appearances of the things & interpreted it in Accor. Dance to aesthetic that Limited by the new method. With those Innovative Visions, & Composite Systems that has Contradiction that take the artistic Work in Spatial anomalies& structural Shifts that blends its Vocabulary in Counteractions, Shift, & disorder, That makes Figurative glitch in accordance to this Contemporary theory which proportions with technology revolution & Scientific technology. The shift appears to find from the artistic figure, whatever its type, whether it is in drawing, carving, or Ceramic, the organization of differences, & the gap of tension happens to give the originality of the work to the inter predation, toward breaking the traditional style which go beyond the Vocabulary of the work breaking the Connected Construction, with modern intellectual trans formations, & here comes the term of Constructional Shift which enters wish the perceptions of the mind to Contribute in Changing the mop of Plastic art, & for the Ceramic art be one of the that its Vocabulary lay multiple choice in reading. For this reason, this Search is Coming: the constructional Shift in Picassos Ceramics. That cant be looking for any ceramic work if there are no operations of reception that lead to read the Ceramic work. It enters the receiver in Conversation with the show, & for this Conversation is active role to give the Ceramic work its meaning, describing it as a result for Communication between the work & its place. Hence, the receiver becomes active member in meaning production operation, to move the work in more than one place for its structural Vocabularies, In mental image, The reading that accomplished is speaking, & this Certainly in